PENGARUH BANYAKNYA PESERTA TES, BUTIR, PILIHAN JAWABAN, SERTA INDEKS KESULITAN TERHADAP STATISTIK DAYA PEMBEDA DAN RELIABILITAS - Ali Hasmy (AT-TURATS, 2014)
This research was conducted to see the effect of the number of testee (sample size), the number of items (test length), the number of options, and index of difficulty to various item discrimination statistics and test reliability. The data used are simulated data and analyzed using the Test Analysis Program (TAP) version 6.65 with a full factorial design. In general, the results show that the number of testee, the number of items, and index of difficulty (except number of options) significantly affect the various item discrimination statistics and test reliability. The statistics are robust to these three factors is only the Mean of Item Discrimination and Spearman Brown’s 1-2 Split-Half, while the most sensitive is Split-Half Odd-Even statistic.